Switchable Friction Coefficient on Shape Memory Photonic Crystals. (2020) - Zhang, Yifan; Lyu, Xingyi; Ni, Yongliang; Li, Diyang; Leo, Sin-Yen; Chen, Yinong; Jiang, Peng; Taylor, Curtis R.
ABSTRACT: Intelligent control of friction and adhesion has attracted much attention for use in soft robotics, human-sensor interfaces, and bionics. Here we introduce a shape memory photonic crystal (SMPC) polymer that can be programmed and recovered by solvent to realize switchable surface friction. Micro sliding test show that the friction coefficient on this SMPC in the programmed and recovered state can vary by three times. We also show that the mechanism behind this switchable friction coefficient is the surface roughness related adhesion.